2020
DOI: 10.4143/crt.2020.080
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATR Increases the Sensitivity to WEE1 Inhibitor in Biliary Tract Cancer

Abstract: Original ArticlePurpose Currently, the DNA damage response (DDR) pathway represents a key target for new cancer drug development. Advanced biliary tract cancer (BTC) has a poor prognosis because of the lack of efficacious treatment options. Although DNA repair pathway alterations have been reported in many patients with BTC, little is known regarding the effects of DDR-targeted agents against BTC. Materials and MethodsIn this study, nine BTC cell lines were exposed to the WEE1 inhibitor (AZD1775). In vitro, MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…4) showed that compared with the control group (Fig. 4 which can easily cause mitotic catastrophe and cell death [10,12]. The results of the Saos2 cell cycle experiment in this study showed that compared with the control group (Fig.…”
Section: Physical Binding Of Wee1 To Rela In Os Cells Is Modulated By Cddp and Wee1 Modulates The Translocation Of Rela Into The Nucleusmentioning
confidence: 53%
See 1 more Smart Citation
“…4) showed that compared with the control group (Fig. 4 which can easily cause mitotic catastrophe and cell death [10,12]. The results of the Saos2 cell cycle experiment in this study showed that compared with the control group (Fig.…”
Section: Physical Binding Of Wee1 To Rela In Os Cells Is Modulated By Cddp and Wee1 Modulates The Translocation Of Rela Into The Nucleusmentioning
confidence: 53%
“…4). This study and others [10][11][12] chemotherapy drugs used to kill cancer cells [13], it is worth noting that large-sample studies have shown extreme heterogeneity among OS patients. Many reports have indicated that the PDX model has strong predictive value for anti-drug resistance in drug response studies [23].…”
Section: Discussionmentioning
confidence: 70%
“…AZD6738, an ATR inhibitor, has shown preclinical activity in panels of BTC cell lines, particularly with SNU478 and SNU869 cell lines (both p53 MUT ) [ 88 ]. The combination of AZD6738 and MK1775 has also been reported to have synergistic effects in p53 MUT BTC cell lines [ 89 ]. Early phase studies of AZD6738 are ongoing in various cancers [ 90 ] and also AZD6738 in combination with durvalumab in BTCs (NCT04298008).…”
Section: Targeting P53 As a Therapeutic Strategymentioning
confidence: 99%
“…Furthermore, a few recent studies have also reported synergistic effects upon combining ATR and WEE1 inhibitors [19][20][21][22]. More specifically, WEE1 and ATR inhibitors caused the synergistic killing of acute myeloid leukemia (AML), biliary tract, and breast cancer cells, likely due to problems arising in S-phase and G2/M [19][20][21]23]. Notably, this combination appears to be well tolerated in mouse models, as it showed little toxicity in normal tissue [19].…”
Section: Introductionmentioning
confidence: 98%